Possible Contribution of Wnt-responsive Chondroprogenitors to The Postnatal Murine Growth Plate - Usami, Yu (J Bone Miner Res, 2019)
Active cell proliferation and turnover in the growth plate is essential for embryonic and postnatal bone growth. We performed a lineage tracing of Wnt/β-catenin signaling responsive cells (Wnt-responsive cells) using Axin2(CreERT2);Rosa26ZsGreen mice and found a novel cell population that resides in the outermost layer of the growth plate facing the Ranvier’s groove (RG, the perichondrium adjacent to growth plate). These Wnt-responsive cells rapidly expanded and contributed to formation of the outer growth plate from the neonatal to the growing stage, but stopped expanding at the young adult stage when bone longitudinal growth ceases. In addition, a second Wnt-responsive sporadic cell population was localized within the resting zone of the central part of the growth plate during the postnatal growth phase. While it induced ectopic chondrogenesis in the RG, ablation of β-catenin in the Wnt-responsive cells strongly inhibited expansion of their descendants toward the growth plate. These findings indicate that the Wnt-responsive cell population in the outermost layer of the growth plate is a unique cell source of chondroprogenitors involving lateral growth of the growth plate, and suggest that Wnt/β-catenin signaling regulates function of skeletal progenitors in a site- and stage-specific manner.